Late presentation of a case of high pressure cement injection injury to the hand - (:unkn) unknown (INFORMA HEALTHCARE, 2013)
High-pressure injection injuries to the upper extremity cause potentially severe complications that result in multiple operations, amputations, and permanent functional deficits. Early exploration and debridement are the mainstays of treatment for optimal functional recovery. We describe the late presentation of a high-pressure cement injection injury to the hand, its management, and long term course.
Keywords: High pressure; injection injury; cement; late referral; claw deformity